The Pengaruh tingkat kepercayaan terhadap kualitas layanan QRIS di Pekanbaru - Sandri, Siti Hanifa; Ardi, Hendri Ali; Syafitri , Roza (Akuntansi & Ekonomika, 2024)
This study aims to analyze the trust of the people of Pekanbaru towards the interest in using QRIS as a payment method. This study uses a quantitative descriptive method to test the influence of trust on the interest in using QRIS. The results show that trust has a positive and significant influence on the interest in using QRIS. People with high levels of trust are more likely to have a higher interest in using QRIS as a payment method. Additionally, this study found that the security and convenience of using QRIS have a positive influence on interest in using it. In a specific context, this study shows that the people of Pekanbaru have high levels of trust in the security and convenience of using QRIS. This means that the people in the city are more confident in using digital payment technologies like QRIS.